The ScHARR LMIC filter: Adapting a low‐ and middle‐income countries geographic search filter to identify studies on preterm birth prevention and management. (26th February 2022) - Sutton, Anthea; Campbell, Fiona
Abstract: Search filters are used to find evidence on specific subjects. Performance of filters can be varied and may need adapting to meet the needs of research topics. There are limited geographic search filters available, and only one pertaining to low‐ and middle‐income countries (LMICs). When searching for literature on preterm birth prevention and management in LMICs for a research project at the School of Health and Related Research (ScHARR), we made use of the Cochrane Effective Practice and Organisation of Care (EPOC) LMIC geographic search filter for the databases; Ovid MEDLINE, Ovid Embase, Cochrane Library. During screening following a broad scoping search in Ovid MEDLINE, it was found that the EPOC LMIC filter did not identify a relevant study. Adaptations were made to the LMIC geographic search filter to maximise retrieval and identify the missing study. Institution was included as a search field, and the search terms high burden or countdown countries were added. The filter was translated for the databases; Ovid Embase, Cochrane Library, Ovid PsycINFO, and CINAHL via EBSCO. The adapted ScHARR LMIC filter is a non‐validated 1st generation filter which increases the sensitivity of the EPOC LMIC search filter. Validating the filter would confirm its retrieval performance and benefit information professionals, researchers, and health professionals. We recommend that the ScHARR LMIC filter is used to improve sensitivity of the Cochrane EPOC LMIC filter and reduce the risk of missing relevant studies.